Pengaruh Kepariwisataan Terhadap Inflasi di Kota Mataram - Baiq Wira Hartati; Lilik Hidayati; Valian Yoga Pudya Ardhana (Universitas Mataram, 2024)
Inflation is part of macroeconomic implementation and is an important variable in developing a fiscal approach. Inflation is the rate of change in cost levels at a certain time compared to cost levels in the previous period. Inflation experiences fluctuations in inflation levels, which can affect people's daily lives. This research aims to determine the level of inflation in the tourism sector in Mataram City for the 2022-2024 period based on the number of guests staying at star hotels. The tourism sector is one of the important pillars of the Indonesian economy, especially in areas that have large tourism potential, namely West Nusa Tenggara (NTB). The data used in this research is secondary data obtained from the Central Statistics Agency (BPS) data on tourism and inflation for the City of Mataram. The analytical method used in this research is simple regression analysis, which is a parametric statistical method to determine the level of relationship between two variables. The results of the analysis show that inflation and tourism have a strong relationship of 0.871 based on the significance level.